Oxytocin reduces alcohol cue-reactivity in alcohol-dependent rats and humans - Hansson, Anita C.; Kiefer, Falk; Sommer, Wolfgang H.; Vollstädt-Klein, Sabine; Spanagel, Rainer (Neuropsychopharmacology, 2018)
Approved pharmacological treatments for alcohol use disorder are limited in their effectiveness, and new drugs that can easily be translated into the clinic are warranted. One of those candidates is oxytocin because of its interaction with several alcohol-induced effects. Alcohol-dependent rats as well as post-mortem brains of human alcoholics and controls were analyzed for the expression of the oxytocin system by qRT-PCR, in situ hybridization, receptor autoradiography ([125I]OVTA binding), and immunohistochemistry. Alcohol self-administration and cue-induced reinstatement behavior was measured after intracerebroventricular injection of 10 nM oxytocin in dependent rats. Here we show a pronounced upregulation of oxytocin receptors in brain tissues of alcohol-dependent rats and deceased alcoholics, primarily in frontal and striatal areas. This upregulation stems most likely from reduced oxytocin expression in hypothalamic nuclei. Pharmacological validation showed that oxytocin reduced cue-induced reinstatement response in dependent rats—an effect that was not observed in non-dependent rats. Finally, a clinical pilot study (German clinical trial number DRKS00009253) using functional magnetic resonance imaging in heavy social male drinkers showed that intranasal oxytocin (24 IU) decreased neural cue-reactivity in brain networks similar to those detected in dependent rats and humans with increased oxytocin receptor expression. These studies suggest that oxytocin might be used as an anticraving medication and thus may positively affect treatment outcomes in alcoholics.
Published: 01 November 2017
Gesehen am 26.07.2018